Profile of Patients Neutropenia Fever Unrelated to Chemotherapy in Dr. Cipto Mangunkusumo General Hospital - Gantira Wijayakusumah Danasasmita; Lie Khie Chen; Robert Sinto; Pringgodigdo Nugroho (Jurnal Penyakit Dalam Indonesia, 2020)
Introduction. The condition of neutropenia increases the risk of infection. The causes of neutropenia are widely discussed as side effects of chemotherapy, but patients with neutropenia who are not due to side effects of chemotherapy are increasing in number. This study aims to provide an overview of the characteristics of neutropenic fever population unrelated to chemotherapy.